Pathogenesis of Apical Periodontitis: a Literature Review - Indre Graunaite; Greta Lodiene; Vita Maciulskiene (eJournal of Oral Maxillofacial Research)
Objectives: This review article discusses the host response in apical periodontitis with the main focus on cytokines, produced under this pathological condition and contributing to the degradation of periradicular tissues. The pace of research in this field has greatly accelerated in the last decade. Here we provide an analysis of studies published in this area during this period.Material and methods: Literature was selected through a search of PubMed electronic database. The keywords used for search were pathogenesis of apical periodontitis cytokines, periapical granuloma cytokines, inflammatory infiltrate apical periodontitis. The search was restricted to English language articles, published from 1999 to December 2010. Additionally, a manual search in the cytokine production, cytokine functions and periapical tissue destruction in the journals and books was performed.Results: In total, 97 literature sources were obtained and reviewed. The topics covered in this article include cellular composition of an inflammatory infiltrate in the periapical lesions, mechanisms of the formation of the innate and specific immune response. Studies which investigated cytokine secretion and functions were identified and cellular and molecular interactions in the course of apical periodontitis described.Conclusions: The abundance and interactions of various inflammatory and anti-inflammatory molecules can influence and alter the state and progression of the disease. Therefore, periapical inflammatory response offers a model, suited for the study of many facets of pathogenesis, biocompatibility of different materials to periapical tissues and development of novel treatment methods, based on the regulation of cytokines expression.